Hypercyclic Behavior of Translation Operators on Spaces of Analytic Functions on Hilbert Spaces - Zoryana Mozhyrovska; Andriy V. Zagorodnyuk (Journal of Function Spaces)
We consider special Hilbert spaces of analytic functions of many infinite variables and examine composition operators on these spaces. In particular, we prove that under some conditions a translation operator is bounded and hypercyclic.